Study of knowledge, attitude, and perception toward LGBTQ people amongst medical students - Reeva Sorathiya; Anup Bharati; Ayushree Patil; Sharad Gorade (Industrial Psychiatry Journal, 2023)
Background: People across cultures have had negative stereotypes, prejudice, and discriminatory attitudes toward the LGBTQ community for many years. Unfortunately, this perception exists within the medical fraternity as well, which in turn has a negative impact on the provision of healthcare facilities to individuals. Change in awareness and perception of LGBTQ among medical undergraduate students may remedy the situation. Aim: To find out the knowledge, attitude, and perception of medical graduates toward the LGBTQ community. Materials and Methods: The study is a cross-sectional observation study and was designed as an online survey using stratified random sampling incorporating the questions from California State University, Northridge (CSUN) questionnaire, Acceptance of Homosexuals (AHO), Homosexuality Attitude Scale (HAS), and relevant sociodemographic details. The data were collected using Google Forms for 3 months. Result: A total of 300 medical undergraduate students were included in the study. Around 87.6% (n = 263) of participants are comfortable having a friend with a homosexual orientation in their circle and 63% (n = 189) disagree that the acceptance of LGBTQ people has anything to do with the morality of our society. Conclusion: Although the overall knowledge and attitude of medical graduates toward LGBTQ is positive, a considerable percentage of students have negative attitudes. Despite the overwhelmingly accepting attitudes and perceptions, some individuals are slightly reluctant to interact comfortably with LGBTQ people. Medical students need to be trained to maintain a non-homophobic attitude.